Aryloxy Alkyl Theophylline Derivatives as Antifungal Agents: Design, Synthesis, Biological Evaluation and Computational Studies. Issue 25 (1st July 2022) - Faghih, Zeinab; Emami, Leila; Zomoridian, Kamiar; Sabet, Razieh; Bargebid, Rahele; Mansourian, Ali; Zeinali, Behnam; Rostami, Zohre; Khabnadideh, Soghra
Abstract: Infectious diseases are still one of the leading causes of death and disability in human society. Synthetic antimicrobial agents have recently emerged as promising candidates against drug‐resistant pathogens. Here we described an efficient procedure for synthesis of aryloxyalkyl theophylline analouges as novel antimicrobial agents. Fourtheen new compounds were synthesized ( 5 a – 5 n ) and their chemical structures were approved by different spectroscopic methods. The synthesized compounds were screened for their antimicrobial activities by broth micro dilution method as recommended by Clinical and Laboratory Standards Institute (CLSI). Molecular docking studies were also performed to forecast their binding modes against cytochrome P450 lanosterol 14α‐demethylase as a main target. The results represented appropriate correlation between molecular docking and antimicrobial activity of the compounds. Based on biological results and in silico ADMET (absorption, distribution, metabolism, excretion, and toxicity) predictions, compound 5 g can be considered as an ideal antimicrobial agent for the future studies. Abstract : A series of aryloxy alkyl theophylline derivatives ( 5 a‐5 n ) were synthesized and evaluated as antimicrobial agents. Compound 5 g represented the high activity (MIC=16 (μg/mL) for A. flavus, A. fumigatus, A. clavatus and also, S. auras microorganisms. Computational study was also done and the results of biological sections were confirmed by the docking study.